El concepto de tiempo más originario en Husserl: la atemporalidad del presente viviente - Ramírez, Manuel (2024)
Husserl‘s reflections on the living present led to its determination as a timeless consciousness that does not actively constitute immanent temporal objects. This characteristic of the original process would imply leaving it outside the transcendental phenomenological field. However, the article tries to show that through an archaeological reconstruction we know that the living present is not only a limit problem, but rather that it passively “constitutes” its temporal objects and is aware of itself through its self-affection, which allows it to insert into the phenomenological-transcendental field.